Ecosystems, Pollution, and Use of Resources in Textbooks of 14 Countries: An Ecocentric Emphasis. (29th January 2012) - Tracana Tracana, Rosa Branca Rosa Branca; Carvalho Carvalho, Graça S. Graça S.
Abstract : Two views of Human-Nature relation can be found: anthropocentrism and ecocentrism. In order to understand how school textbooks refer to the human's position in nature we analysed how "Human as guest versus Humans as owners of nature" is present in the three topics of environmental education— Ecosystems, Pollution, and Use of Resource —in textbooks of 14 countries from Europe, Africa, and Middle East. A specific grid of analysis, which was constructed in the context of the European Project BIOHEAD-CITIZEN, was used in this study. Results show that this axis of analysis is present in the majority of textbooks addressing the above three topics but not in the " Biodiversity " topic. Textbooks for 12–15-year old pupils were the ones having more occurrences than those for 6–11- or 16–18-year olds. The textbooks present mainly an ecocentric position, whereas the aesthetic, ethical, and cultural aspects are limited and inadequate, limiting the full perspective of education for sustainable development.